Ecological and economic assessments of biological resources in the North Pacific and strategies for their use - I. V. Volvenko (Известия ТИНРО)
New attempt to answer the questions: 1) what aquatic biological resources are possessed in the Russian Far-Eastern Seas and North Pacific and what is their quantity? 2) which of them and how many are caught annually? 3) are these resources managed rationally in Russia? 4) and what is the reason for current situation and can it be improved? Based on the data of trawl surveys, a GIS is created with maps of the biological resources distribution, separately for actually harvested, potentially commercial, and non-commercial ones. The biomass, potential yield and its cost are calculated for the Chukchi, Bering, Okhotsk, and Japan Seas and North-West Pacific. These water bodies are ranked by their value for commercial fisheries. The obtained estimates are compared with the data on annual catch, export, import, and consumption of fish products in Russia. Possibility of larger landing is concluded for each water body, in terms of the harvested species biomass. The harvest from the Okhotsk Sea alone can reach more than 5.2 million tons that exceeds the level of «strategic ceiling» for the entire Russian fishery proposed in «Strategy for development of the fisheries complex of Russian Federation for the period to 2030». For the whole water area under consideration, this level can be exceeded by 3.5–4.7 times, or even by 5.6 times if the potentially commercial species will be exploited. Dynamics of domestic catch, trade and consumption of the biological resources are analyzed. The conclusion is that socioeconomic conditions rather than the state of biological resources are the reason that Russia still does not harvest so much. Some measures are proposed to improve the management of the Russian fishery industry. The obtained results cah alsobe used for maintenance rational use of the biological resources, food security, and nature protection, including evaluation of cost for biological resources in certain water bodies and assessment of damage caused to the nature and biological resources by pollution, construction, oil and gas production, or technogenic accidents.